Method of explanation in biological systems as applied on medical sciences - Shogar, Ibrahim; Abdul Rahman, Suzanah (2021)
For practical purposes, philosophers of science differentiate between three modes of biology: (i) functional; (ii) evolutionary; and (iii) systems biology. This classification is based on the nature of biological process. This paper aims to highlight these categories and investigate the way it may contribute in developing the objective method of explaining the biological systems for better life on earth. Study of biological systems is necessary, not only for its medicinal implications to promote the environmental and human health, but also for better management of social changes. Understanding the governing principles of biological processes and codified systems of living organism is necessary for predication and control, which are major characteristics of scientific explanation. Medical sciences are based on understanding the biological processes at both levels of the programmed systems of natural biology, as well as the conscious acts of human being. It is no doubt that modern biotechnology plays a crucial role both in the elucidation of the molecular causes of disease and in the development of new diagnostic methods and better targeted drugs (David Playfair, 2008). The major challenge that has been facing efforts on harnessing the biological phenomenon is embedded not only in complexity of the biological phenomenon, but also lacking the relevant method of explanation. Accordingly, predication and control have been the major problems of this field. This paper aims at investigating problems of explanation and prediction in biological processes, as related to the above classifications of biology, with especial focus on medical sciences. Contribution of systems biology and evolutionary biology in understanding the biological processes and its implications on health sciences will be highlighted. The paper adopts the theoretical method of analysis. The relevant texts on systems biology and evolutionary biology will be reviewed. The paper presupposes that the new developments on systems biology can contribute in developing a measurable method explanation which enables to predict and control in all complex fields of the natural phenomena, which named by Ernst Mayr as “irregular subjects”.